Peran Internasional Monetery Fund (IMF) dalam Mendukung Pembangunan Ekonomi di Negara Berkembang - Ridwan, Muhammad; Nurhayati, Dies (Journal of Islamic Economics Studies and Practices, 2025)
This article discusses the role of developing countries' economic development supported by the International Monetary Fund (IMF). In the era of globalization, developing countries face challenges such as financial market volatility and limited resources. The IMF, founded in 1944, plays a key role in providing loans, technical assistance, research, analysis, and surveillance to strengthen the economic policies of its member countries. This article uses a qualitative method by examining sources from various reference journals to understand the impact and criticism of the role of the IMF. The results show that while the IMF has helped developing countries overcome financial crises and boost economic growth, its policies and requirements are often seen as exacerbating the conditions of countries in crisis. Despite these criticisms, the IMF continues to play a role in creating global economic stability. This article also reviews the history of the IMF, its short- and long-term policies, and the impact of IMF assistance on several countries. In conclusion, the IMF needs to continue to adapt and innovate in order to support inclusive and sustainable economic growth.